Use of mobile phones and television for essential obstetric care among women availing maternal and child health services at a rural maternity hospital in South Karnataka - Arasu, Sakthi; Jain, Ashmika; Lakra, Sunita; Sophia, Antony; Johnson, Avita Rose (Indian Journal of Community Health, 2019)
Background: To improve on Maternal and Neonatal Mortality Rates, newer technologies need to be explored to achieve Sustainable Development Goals of 2030. Objectives: To assess the use of mobile phones for essential obstetric care and associated factors among women availing obstetric services at a rural maternity hospital in South Karnataka. Material & Methods: A cross sectional study was done among the women availing obstetric services in Snehalaya Hospital, Solur in Ramnagara District. Results: There were 236 women included in the study, with a mean age 23.3 (3.22) and 11.78 (2.87) mean years of completed education. 99.15% had mobile phones but only 65% among them had their own phone. None of the women received text messages from MCTS (Government MCH Texts). Of the 53.4% women who had smartphone at home, only 42.4% used the smartphone to search for general health information and none of them used their mobile phone to access essential obstetric care. 48.2% watched health related advertisements and promotions on TV. Antenatal care was adequate among the women, but birth preparedness was found to be poor. Conclusion: The rural women in this study had poor utilization of mobile phones in obstetric care despite the presence of smartphones at home.